1956
DOI: 10.2136/sssaj1956.03615995002000020026x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Growth and Production as Affected by Moisture, Nitrogen, and Plant Spacing on the Yuma Mesa

Abstract: Acala 44 cotton was grown near Yuma, Ariz. on irrigated Superstition loamy sand having a steep productivity gradient from one end of the field to the other. Effects of soil moisture, N rate, and plant spacing, each at 3 levels in a factorial experiment, were determined for vegetative growth, fruiting, N uptake, yields, and ginning and fiber characteristics. Yields were increased substantially by N, and significantly, but less so by moisture and spacing. The spacing effect was limited to the second of 2 picking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
1

Year Published

1961
1961
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
2
16
0
1
Order By: Relevance
“…Hamilton et a!. (7) working under conditions of limited plant growth found no differences in flowering or boll set in cotton irrigated 41, 21 or 12 times.…”
mentioning
confidence: 94%
“…Hamilton et a!. (7) working under conditions of limited plant growth found no differences in flowering or boll set in cotton irrigated 41, 21 or 12 times.…”
mentioning
confidence: 94%
“…Harris and Hawkins (1942) and Hamilton et al (1956) found in Arizona that early irrigations, which induced good vegetative growth before fruiting, also increased cotton yields. However, Thornton (1961) found that cotton needed a good supply of moisture during the boll setting period, until about three-fourths of the bolls were mature, whereas moderate drought in the early growing period did little harm.…”
mentioning
confidence: 99%
“…The optimum is a finite quan• tity when the regression of yield of lint on the amount of N applied is curvilinear. Linear relationships have been reported ( 6,11) . The optimum amount of P required by cotton is affected by the accompanying application of N (2,4,5).…”
Section: Review Of Literaturementioning
confidence: 87%